Plexiform neurofibroma as a cause of carpal tunnel syndrome in a radial deficiency patient. (4th May 2019) - Hu, Kejia; Ma, Hao; Shen, Yundong; Williams, Ziv; Xu, Wendong
Abstract: We reported a rare peripheral nerve case, a patient developed carpal tunnel syndrome with a history of floating thumb in right hand. The median nerve was found expanded and spindle-shaped and a plexiform neurofibroma was diagnosed. Our case sheds light on anatomy and possible etiological association which may help clinical management.